Debating nationalism : the global spread of nations - Bieber, Florian (London, England : Zed Books, 2020)
This concise introduction offers an overview of the global rise and spread of nationalism since the late 18th century. Reflecting on key themes and existing scholarship it presents case studies and primary sources to track the emergence of the modern nation, and understand how nationalism has given rise to phenomena such as identity-based conflict, authoritarian politics and populist movements. Debating Nationalism uses an inclusive perspective that goes beyond a Western European focus to explore how nationalism has expressed itself in nation states and influenced a range of political ideologies over the last 300 years. It engages with the key debates within nationalism studies such as the origins of nations, the mechanisms and actors that reinforce it and the dynamics of ethnic conflict. Using a historical lens to shed light on contemporary issues, it also considers debates around migration, diversity and authoritarian politics found in new nationalism in the modern day. This book includes a dedicated chapter as a guide to key debates and further reading alongside a glossary of terms to help students achieve a holistic understanding of the history of nationalism. --
The beginnings of nationalism and nations -- The spread of nationalism and nation-states in Europe -- The global spread of nationalism and decolonization -- Nationalism after the establishment of the nation-state -- Ethnic conflict -- Migration and the politics of diversity -- New nationalism and populism.
Includes bibliographical references (pages [219]-238) and index
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Nationalism -- History; Nationalism; General & world history; Electronic books